The Effect of Social Media Marketing, Brand Image, Promotion, Competitive Advantage, and Service Quality on Firm Performance - Kesumahati, Erilia; Jacky, Jacky; Putra, Edy Yulianto (Ekonomis: Journal of Economics and Business, 2025)
This study aims to analyze the influence of social media marketing, brand image, promotion, competitive advantage, and service quality on the performance of international travel agents. Data were collected directly by sending an online questionnaire via Google Forms. Respondents included supervisors, managers, and owners who actively manage the agency's social media accounts. The study sample consisted of 107 qualified respondents and was analyzed using Partial Least Squares-Structural Equation Modeling (PLS SEM). The findings indicate that brand image, promotion, competitive advantage, and service quality each have a positive and significant influence on company performance; in contrast, social media marketing does not show any such influence. These results underscore the dominance of brand image, promotion, competitive advantage, and service quality in driving performance in the international travel sector.